2020
DOI: 10.1039/d0ra04890a
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterisation of PHT-loaded chitosan lecithin nanoparticles for intranasal drug delivery to the brain

Abstract: The use of nanoparticles (NPs) for intranasal (IN) drug delivery to the brain represents a hopeful strategy to enhance brain targeting of anti-epileptic drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 54 publications
(80 reference statements)
0
21
0
Order By: Relevance
“…Nanoparticles were present in the nasal cavity for up to 24 h, allowing additional time for them to reach the brain [149]. Similarly, chitosan-lecithin NPs for brain targeting loaded with phenytoin demonstrated relatively high accumulation in brain and low phenytoin levels in plasma after intranasal delivery as compared to intraperitoneal injection, which produced initial high plasma levels before crossing the blood-brain barrier [150]. The intraocular delivery of chitosan inserts radiolabeled with Tc-99m resulted in the retention of NPs for up to 6-8 h at the site of instillation in the eye, after which the formulation accumulated in the gastrointestinal tract, mainly the large intestine, via nasolacrimal clearance [151,152].…”
Section: Effect Of Mucosal Routes Of Administrationmentioning
confidence: 99%
“…Nanoparticles were present in the nasal cavity for up to 24 h, allowing additional time for them to reach the brain [149]. Similarly, chitosan-lecithin NPs for brain targeting loaded with phenytoin demonstrated relatively high accumulation in brain and low phenytoin levels in plasma after intranasal delivery as compared to intraperitoneal injection, which produced initial high plasma levels before crossing the blood-brain barrier [150]. The intraocular delivery of chitosan inserts radiolabeled with Tc-99m resulted in the retention of NPs for up to 6-8 h at the site of instillation in the eye, after which the formulation accumulated in the gastrointestinal tract, mainly the large intestine, via nasolacrimal clearance [151,152].…”
Section: Effect Of Mucosal Routes Of Administrationmentioning
confidence: 99%
“…In another recent study, chitosan–lecithin nanoparticles loaded with the anti-seizure medication phenytoin were intranasally administered in conscious mice [ 24 ]. The drug delivery of phenytoin is particularly challenging due to the drug’s low aqueous solubility and tendency to crystallize, causing slow absorption and post-injection pain.…”
Section: Methods To Combat Structural Chemical and Transport-mediated Challenges Of Drug Delivery Across The Bbbmentioning
confidence: 99%
“…Additionally, phenytoin is both highly protein-bound and classified as a Pgp substrate, resulting in low brain bioavailability. However, the study found that the intranasal administration of phenytoin-loaded chitosan–lecithin nanoparticles in BALBc mice resulted in a rapid accumulation of phenytoin in the mouse brain after 5 and 60 min, along with sustained concentrations 72 h after administration [ 24 ].…”
Section: Methods To Combat Structural Chemical and Transport-mediated Challenges Of Drug Delivery Across The Bbbmentioning
confidence: 99%
“…Nasal drug delivery is a non-intrusive technique of delivering drugs to the respiratory system, the central nervous system (CNS), and/or systemic circulation [ 189 ]. Intranasal delivery offers direct to brain drug delivery via intracellular and extracellular pathways, involving transcellular, paracellular, and extracellular transport mechanisms alongside the olfactory and trigeminal nerve fibers [ 190 ].…”
Section: Opportunities For Cross-linked Gels In Cns Drug Deliverymentioning
confidence: 99%